Bergey's Manual of Systematics of Archaea and Bacteria 2015
DOI: 10.1002/9781118960608.gbm01145
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacter

Abstract: En.te.ro.bac' ter . Gr. neut. n. enteron intestine; M.L. masc. n. bacter equivalent of bacterium, a small rod; M.L. masc. n. Enterobacter intestinal small rod. Proteobacteria / Gammaproteobacteria / Enterobacteriales / Enterobacteriaceae / Enterobacter Straight rods, 0.6–1.0 × 1.2–3.0 µm, conforming to the general definition of the family Enterobacteriaceae . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…These properties nearly corresponded to Kosakonia cowanii. This was further corroborated by the phylogenetic analysis, which resolved P-37 within the clade with other K. cowanii isolates (Figure 1) [25]. Therefore, we concluded that this strain belongs to K. cowanii.…”
Section: Number and Type Of Bacteria Living On Buckwheat Sproutssupporting
confidence: 75%
“…These properties nearly corresponded to Kosakonia cowanii. This was further corroborated by the phylogenetic analysis, which resolved P-37 within the clade with other K. cowanii isolates (Figure 1) [25]. Therefore, we concluded that this strain belongs to K. cowanii.…”
Section: Number and Type Of Bacteria Living On Buckwheat Sproutssupporting
confidence: 75%
“…As previously described [2], the presence of Bchl a and carotenoid pigment was determined for in vivo whole cells and acetone–methanol extracts with a spectrophotometer (S-3100, Scinco) for cells that had been grown in either the dark or the light for 7 days. Voges–Proskauer (VP) reaction was tested as previously described [26] with negative and positive control strains ( Escherichia coli KCCM 11234 T and Enterobacter aerogenes KCCM 12177 T , respectively) [28, 29]. H 2 S production assay was performed using triple sugar iron agar (Difco) with negative and positive control strains ( Escherichia coli KCCM 11234 T and Citrobacter freundii KCCM 11931 T , respectively) [28, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Specific media can also be employed for the isolation of the Enterobacteriaceae e.g. MacConkey and Hektoen media that are specifically designed for P. ananatis isolation (Grimont and Grimont 2015). In general, isolation of bacteria from infected plants is mainly carried out using nutrient agar (Bruton et al 1991;Gitaitis and Gay 1997;Schaad 2001;Countinho et al 2002).…”
Section: Phenotype Characteristics Isolationmentioning
confidence: 99%